Treatment of a Recurrent Vaginal Obstruction With a Modified Mold After an Excision of a Transverse Vaginal Septum - Megadhana, I Wayan (BALI MEDICAL JOURNAL, 2016)
Background: A vaginal obstruction often occurs as a complication in women who had previously undergone an excision of a transverse vaginal septum. The use of a mold coated with membranes in the correction surgery provides a good healing prognosis. Objective: To report a case of a treatment of a recurrent vaginal obstruction with a modified mold after undergoing an excision of a transverse vaginal septum in a 15-year-old woman. Result: A follow-up on the patient, four months after using the modified mold, showed a regular menstrual cycles without a sign of vaginal narrowing, an infection, nor a complaint. Conclusion: The treatment using a modified mold, for a recurrent vaginal obstruction after an excision of a transverse vaginal septum, is a new innovation with a satisfactory result.